GSH-responsive targeted copper-based nanoparticle improve ovarian cancer treatment via induction of apoptosis-ferroptosis-cuproptosis - Li Ma; Sihong Guo; Xinlei Yang; Hongyu Gao; Jie Chen (Materials & Design)
The combination of apoptosis-ferroptosis-cuproptosis provides a beneficial method for enhancing the curative effect of ovarian cancer (OC). In this study, we design and synthesize a nano-drug delivery platform, HTC@DOX, which is achieved by the self-assembly of an amphipathic molecule HA-SS-TOS-DTPA, Cu2+, and doxorubicin (DOX). HTC@DOX bring the combination of chemotherapy (CT) from DOX and the chemodynamic therapy (CDT) from Cu2+. In vitro and in vivo experimental results show that HTC@DOX have excellent stability and glutathione responsiveness. This platform efficiently and purposely targets tumor sites, and destroy OC cells through the synergy of CT and CDT by induce apoptosis-ferroptosis-cuproptosis, thus enhancing the anti-cancer efficacy with a tumor reduction rate of 92.3 %. In addition, the results of electrocardiogram, ultrasound and histopathological staining demonstrate that HTC@DOX have superior biological safety and alleviate the cardiotoxicity caused by DOX alone. The results of bulk RNA sequencing and western blot show the alterations of apoptosis, ferroptosis, and cuproptosis related indicators, which further corroborates the anti-tumor efficacy of HTC@DOX. In brief, this study verifies the feasibility and effectiveness of the combination of CT and CDT in the treatment of OC by inducing apoptosis-ferroptosis-cuproptosis, offering an innovative approach for the treatment of cancer.